2015
DOI: 10.1016/j.freeradbiomed.2015.03.008
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacterium tuberculosis has diminished capacity to counteract redox stress induced by elevated levels of endogenous superoxide

Abstract: Mycobacterium tuberculosis (Mtb) has evolved protective and detoxification mechanisms to maintain cytoplasmic redox balance in response to exogenous oxidative stress encountered inside host phagocytes. In contrast, little is known about the dynamic response of this pathogen to endogenous oxidative stress generated within Mtb. Using a noninvasive and specific biosensor of cytoplasmic redox state of Mtb, we for first time discovered a surprisingly high sensitivity of this pathogen to perturbation in redox homeos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
80
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 80 publications
(91 citation statements)
references
References 55 publications
4
80
1
Order By: Relevance
“…S3). 22 [27][28][29][30][31][32][33][34][35]. Consistent with previous observations that both nitro groups were necessary for decomposition, we found that 9j-9l gave 1 mol of SO 2 per mol of compound (Table 2, entries 36-38).…”
Section: Introductionsupporting
confidence: 90%
See 1 more Smart Citation
“…S3). 22 [27][28][29][30][31][32][33][34][35]. Consistent with previous observations that both nitro groups were necessary for decomposition, we found that 9j-9l gave 1 mol of SO 2 per mol of compound (Table 2, entries 36-38).…”
Section: Introductionsupporting
confidence: 90%
“…Induction of redox stress through enhancement of reactive oxygen species (ROS) 29,35 or reactive nitrogen species (RNS) has been considered as a possible mechanism for developing new anti-bacterials. [36][37][38][39] Ours is the first report of MRSA being sensitive to sulfur dioxide, a reactive sulfur species.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that increases in endogenous ROS can have significant and detrimental results on Mtb growth and viability in vitro and during infection (Vilcheze, et al, 2013) (Tyagi, et al, 2015). To measure intracellular ROS formation in Mtb, the fluorescent dye CellROX green was employed (Saini, et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…The transcriptional profiling data and potentiation of oxidation agents suggests that AC2P36 may promote the accumulation of intracellular reactive oxygen species (ROS). Recent studies have shown that increases in endogenous ROS can have significant and detrimental results on Mtb growth and viability in vitro and during infection (Vilcheze, et al, 2013) (Tyagi, et al, 2015). To measure intracellular ROS formation in Mtb, the fluorescent dye CellROX green was employed (Saini, et al, 2016).…”
Section: Ac2p36 Causes Accumulation Of Intracellular Reactive Oxygen mentioning
confidence: 99%